Bremsstrahlung emission and plasma characterization driven by moderately relativistic laser–plasma interactions. (6th January 2021) - Singh, Sushil; Armstrong, Chris D; Kang, Ning; Ren, Lei; Liu, Huiya; Hua, Neng; Rusby, Dean R; Klimo, Ondřej; Versaci, Roberto; Zhang, Yan; Sun, Mingying; Zhu, Baoqiang; et al.
Abstract: Relativistic electrons generated by the interaction of petawatt-class short laser pulses with solid targets can be used to generate bright x-rays via bremsstrahlung. The efficiency of laser energy transfer into these electrons depends on multiple parameters including the focused intensity and pre-plasma level. This paper reports experimental results from the interaction of a high intensity petawatt-class glass laser pulses with solid targets at a maximum intensity of 10 19 W cm −2 . In-situ measurements of specularly reflected light are used to provide an upper bound of laser absorption and to characterize focused laser intensity, the pre-plasma level and the generation mechanism of second harmonic light. The measured spectrum of electrons and bremsstrahlung radiation provide information about the efficiency of laser energy transfer.